2020
DOI: 10.1098/rspb.2020.0397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urban habitat use on parasitism in mammals: a meta-analysis

Abstract: Rates of urbanization are increasing globally, with consequences for the dynamics of parasites and their wildlife hosts. A small subset of mammal species have the dietary and behavioural flexibility to survive in urban settings. The changes that characterize urban ecology—including landscape transformation, modified diets and shifts in community composition—can either increase or decrease susceptibility and exposure to parasites. We used a meta-analytic approach to systematically assess differences in endopara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 104 publications
3
49
1
Order By: Relevance
“…These contrasting results show that the effect of Monterey pine plantations on parasitism is parasite-dependent, which might be consequence of differences in the ecology, life cycle and other attributes between parasite species and their relation to the environment and their hosts. In fact, the effects of land-use change on helminth parasitism depend on the life history traits of each host–parasite association, as shown in several studies across the world [ 3 , 35 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These contrasting results show that the effect of Monterey pine plantations on parasitism is parasite-dependent, which might be consequence of differences in the ecology, life cycle and other attributes between parasite species and their relation to the environment and their hosts. In fact, the effects of land-use change on helminth parasitism depend on the life history traits of each host–parasite association, as shown in several studies across the world [ 3 , 35 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic land-use change can impact biodiversity and human health, being a major driver of biodiversity loss and zoonotic disease emergence [ 1 ] Land-use change can modify host–parasite interactions through a variety of mechanisms that involve changes in abundance, behavior and immune response of hosts, as well as the composition and structure of host community [ 2 ]. Additionally, land-use change can modify abiotic conditions, which, in turn, may influence the transmission and life cycle of parasites such as helminths, which have several life stages with close contact with the environment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In rural areas, close proximity to livestock (and close proximity between livestock and wildlife) regularly exposes poor populations with potentially limited healthcare access to a number of zoonotic diseases. 17 In human-dominated areas, wild species that survive land conversion are predisposed to high stress and weaker immune systems, 18 reduced fear of humans, 19 and ultimately, to hosting zoonotic pathogens. 20 Together, these trends have driven a massive increase in infectious disease at the human-livestock-wildlife interface.…”
Section: Spillover Pandemics and Global Changementioning
confidence: 99%
“…Because our analysis examined between-species variation, the underlying phenotypes of mammal species that allow them to colonise urban environments (e.g., small size, fast life history, diet generalism; Santini et al 2019) could produce our results by inherently encouraging a greater pathogen diversity, rather than urban affiliation driving greater pathogen diversity per se. This problem could be addressed through broad meta-analyses of within-species variation in immunity and disease across urbanisation gradients, which have thus far examined a relatively small number of species and focused primarily on pathogens rather than immunity (Murray et al 2019;Werner & Nunn 2020). However, our models included a number of fixed effects (body mass, taxonomy, life history, diet diversity) that were previously found to influence urban adaptation probability (Santini et al 2019), and revealed an urban bias to pathogen diversity that was additional to these effects.…”
Section: Discussionmentioning
confidence: 99%